2006
DOI: 10.2514/atcq.14.2.117
|View full text |Cite
|
Sign up to set email alerts
|

The Future Oceanic ATC Environment: Analysis of Mixed Communication, Navigation, and Surveillance Equipage

Abstract: Technical capabilities for significant improvements in communication, navigation, and surveillance (CNS) over the oceans are currently available through the use of satellites. However, all aircraft operators will not equip simultaneously because of the high costs required. Consequently, as these CNS systems are integrated into the oceanic air transportation architecture, the controller will have to manage a mixed equipage fleet. Also, planned reductions in separation minima are based on aircraft equipage, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Equipped aircraft in the study were outfitted with the Future Air Navigation System (FANS-1A) avionics package and datalink. The study found the 50% equipage scenario had the most reports of difficulty and loss of situation awareness [Forest and Hansman, 2006]. Based on these results, the authors recommend further exploring airspace segregation as a means of reducing the complexity of the mixed equipage environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equipped aircraft in the study were outfitted with the Future Air Navigation System (FANS-1A) avionics package and datalink. The study found the 50% equipage scenario had the most reports of difficulty and loss of situation awareness [Forest and Hansman, 2006]. Based on these results, the authors recommend further exploring airspace segregation as a means of reducing the complexity of the mixed equipage environment.…”
Section: Introductionmentioning
confidence: 99%
“…Simpler assumptions about the airspace should result in fewer complications during offnominal events, and reduce controller workload and confusion during normal operations. Forest and Hansman suggest that, as a side benefit, efficient segregated airspace could also encourage users to invest in advanced equipage [Forest and Hansman, 2006]. However, segregated airspace could come at a significant cost in underutilized airspace capacity and in reduced user flexibility because such partitioning, by definition, limits access to all users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research into the feasibility of integrated airspace is warranted to determine whether aircraft with different levels of equipage can co-exist in the same airspace and under what conditions this may be possible 31 . Prior literature on mixed equipage or mixed operations airspace has shown initial feasibility in some studies 33,34 and uncovered feasibility issues in others 35,36 . A study was conducted in 2008 to examine the implications of mixed equipage on airspace configuration requirements for advanced separation assurance operations, particularly under higher traffic densities.…”
Section: Mixed Equipage Operations Of Automation-separated and Contromentioning
confidence: 99%